Key factors for species distribution modeling in benthic marine environments - Tong, Ruiju; Yesson, Chris; Yu, Jinsongdi; Luo, Yuan; Zhang, Ling (Frontiers in Marine Science, 2023)
Species distribution modeling is a widely used technique for estimatinge the potential habitats of target organisms based on their environmental preferences. These methods serve as valuable tools for resource managers and conservationists, and their utilization is increasing, particularly in marine environments where data limitations persist as a challenge. In this study, we tookemployed the global distribution predictions of six cold-water coral species as a case study to investigate various the impacting factors influencingin predictions, including the modeling algorithms, background points sampling strategiesy and sizes, and the collinearity of environmental datasets, using both discriminative performance metrics and functional performance metrics. The Cchoice of background sampling method exhibits a stronger influence on themodel performance, compareding to the effects of modeling algorithms, size of background point sampling sizes, or the collinearity of the environmental dataset. Predictions that utilize kernel density backgrounds, maintain an equal number of presences and background points for algorithms of GBMBRT, RF, and MARS, and employ a substantial number of background points for MAXENT, coupled with a collinearity -filtered environmental dataset in species distribution modeling, yieldare of higher levels of discriminative and functional performance. Overall, BRT and RF outperformed MAXENT, a conclusion that is further substantiated by the analysis of smoothed residuals and the uncertainty associated with the This is a provisional file, not the final typeset article predicted habitat suitability of Madrepora oculata. This study offers valuable insights for enhancing species distribution modeling in marine benthic environments,thereforebeneficial for thereby benefiting for resource management and conservation strategies for benthic species.